2012
DOI: 10.7314/apjcp.2012.13.1.157
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Pooled Analysis of Glutathione S-transferase Genotype Polymorphisms and Risk of Adult Gliomas

Abstract: Objective: Glutathione S-transferases (GSTs) are multifunctional enzymes that play a crucial role in the detoxification of both the endogenous products of oxidative stress and exogenous carcinogens. Recent studies investigating the association between genetic polymorphisms in GSTs and the risk of adult brain tumors have reported conflicting results. The rationale of this pooled analysis was to determine whether the presence of a GST variant increases adult glioma susceptibility by combining data from multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Among these enzymes, Glutathione-S-transferase (GST) is important for detoxifying exogenous and endogenous substances and protecting cells from the toxic effects of ROS (Narasimhan et al, 2011;Yao et al, 2012). The main function of these enzymes is to catalyze the formation of glutathione-S-conjugates with electrophiles, which is crucial for inactivation and subsequent excretion of these molecules (Koh et al, 2011;Nosheen et al, 2011).…”
Section: Expression Of Cyp1a1 and Gstp1 In Human Brain Tumor Tissues mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these enzymes, Glutathione-S-transferase (GST) is important for detoxifying exogenous and endogenous substances and protecting cells from the toxic effects of ROS (Narasimhan et al, 2011;Yao et al, 2012). The main function of these enzymes is to catalyze the formation of glutathione-S-conjugates with electrophiles, which is crucial for inactivation and subsequent excretion of these molecules (Koh et al, 2011;Nosheen et al, 2011).…”
Section: Expression Of Cyp1a1 and Gstp1 In Human Brain Tumor Tissues mentioning
confidence: 99%
“…Elevated expression of GSTs has been implicated in resistance to apoptosis initiated by a variety of stimuli (Francis et al, 1995). In addition, these enzymes are thought to play a role in detoxification and protecting DNA from oxidative damage (Yao et al, 2012). Other important enzyme involved in detoxification is the cytochrome P450 1A (CYP1A1) family of proteins which are involved in the bioactivation and detoxification of environmental toxins to the generation of chemical carcinogens (Shukla et al, 2013).…”
Section: Expression Of Cyp1a1 and Gstp1 In Human Brain Tumor Tissues mentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) have identified various new susceptibility regions (Wrensch et al, 2009;Rajaraman et al, 2012). Genes involved in the cell cycle and DNA repair, have been proposed to play role in glioma pathogenesis and progression, such as glutathione S-transferases(GSTs), excision repair cross-complementing rodent repair deficiency complementation group 1(ERCC1), X-ray repair cross-complementing groups 1(XRCC1) and X-ray repair cross-complementing groups 3 (XRCC3) (Wrensch et al, 2004;Custódio et al, 2011;Zhou et al, 2011;Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated expression of GST has been implicated in resistance to apoptosis initiated by a variety of stimuli. In addition, GST thought to play an important function in detoxification and protecting DNA from oxidative damage [6]. In our present study we performed ELISA analysis for the determination of expression of specific activity of GSTs in HNSCC, which is involved in carcinogen detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Glutathione-S-transferase (GST) is significant for detoxifying exogenous and endogenous substances and protecting the cells from toxic effects of ROS [6,7]. The key role of GST is to catalyze the formation of glutathione-S-conjugates with electrophiles that is decisive for inactivation and consequent excretion of other molecules [8,9].…”
Section: Introductionmentioning
confidence: 99%